A Product Development Model of Denim Jeans for The Indian Market - Mohamed Rasim; Renjini Girija (Universitas Pendidikan Indonesia (UPI), 2023)
Product development is an essential process in producing a marketable product. The study proposes a new product development model incorporating customer requirements and market trends for developing a new jeans range. The data on consumer preference of denim jeans was collected by employing a survey. The consumer survey provided insights into fit, colour, washing tone and style preference, wearing patterns, buying behaviour and sustainability requirements. Further, a web scraping algorithm was used to collect data on competitive online products. The features of jeans sold in the online market in India were studied. The data analysis provided the basis for feature selection for the denim jeans samples. These features provided the base for developing a new jeans range for men and women. Potential consumers wore the newly designed jeans, and feedback was collected. The method of competition mapping described in this study is economical and effective for forecasting trends. The proposed product development model has practical applications and is affordable for all brands.